The association of maternal age, body mass index, physical activity with Gestational Diabetes Mellitus - Hina Hazrat; Sadaf Ahmed; Shamoon Noushad (International Journal of Endorsing Health Science Research, 2018)
Background: Gestational diabetes mellitus (GDM) represents the state of carbohydrate intolerance during gestation. GDM is found as a risk factor for adverse outcomes of gestation concerning maternal and fetal health conditions. Increasing maternal age is found associated with GDM and also other obstetric complications. High maternal weight is reported to be linked to elevated risk of GDM. Relation of increased maternal age and elevated body mass index (BMI) state with GDM suggests a need of effective measures for improving the maternal and fetal health conditions and alienate the GDM associated obstetric concerns. Previous studies have found possible role of physical activity and exercise in reducing the risk of GDM development. This study aimed to explore GDM prevalence among participants and to perform comparative analysis of maternal age and BMI between participants without GDM and participants with GDM.